Enhancing ESP Students’ Critical Thinking and Communication skills through AI-Supported Case-Based Learning - Isnaini Eddy Saputro; Desi Surlitasari Dewi; Tiara Nove Ria; Mohammed Abbas Mahdi (Jurnal Pemberdayaan Masyarakat, 2026)
This study examined the effectiveness of Case-Based Learning (CBL) integrated with artificial intelligence (AI) tools in enhancing critical thinking and communication skills among English for Specific Purposes (ESP) students in higher education. The study was motivated by the growing need for ESP students to develop advanced reasoning and practical communication skills to meet academic and professional demands. Using a quasi-experimental pre-test–post-test control-group design, 237 ESP students participated, with 119 assigned to the experimental group and 118 to the control group. Over six weeks, the experimental group engaged in AI-supported CBL, while the control group received conventional CBL without AI tools. Data were collected using a critical thinking test adapted from the Watson–Glaser framework and a communication skills rubric and analyzed using Welch’s t-tests. The results showed statistically significant improvements in critical thinking (t = 25.567, p .001) and communication skills (t = 24.981, p .001) in the experimental group compared to the control group. The findings confirm that AI-supported CBL has a substantial impact on students’ higher-order thinking and communicative performance. This study contributes to ESP pedagogy by providing empirical evidence that integrating AI tools into CBL serves as an effective instructional model.